Oxfendazole mediates macrofilaricidal efficacy against the filarial nematode Litomosoides sigmodontis in vivo and inhibits Onchocerca spec. motility in vitro. - Marc P Hübner; Coralie Martin; Sabine Specht; Marianne Koschel; Bettina Dubben; Stefan J Frohberger; Alexandra Ehrens; Martina Fendler; Dominique Struever; Edward Mitre; Nathaly Vallarino-Lhermitte; Suzanne Gokool; et al. (Public Library of Science (PLoS), 2020)
A major impediment to eliminate lymphatic filariasis and onchocerciasis is the lack of effective short-course macrofilaricidal drugs or regimens that are proven to be safe for both infections. In this study we tested oxfendazole, an anthelmintic shown to be well tolerated in phase 1 clinical trials. In vitro, oxfendazole exhibited modest to marginal motility inhibition of adult worms of Onchocerca gutturosa, pre-adult worms of Onchocerca volvulus and Onchocerca lienalis microfilariae. In vivo, five days of oral treatments provided sterile cure with up to 100% macrofilaricidal efficacy in the murine Litomosoides sigmodontis model of filariasis. In addition, 10 days of oral treatments with oxfendazole inhibited filarial embryogenesis in patent L. sigmodontis-infected jirds and subsequently led to a protracted but complete clearance of microfilaremia. The macrofilaricidal effect observed in vivo was selective, as treatment with oxfendazole of microfilariae-injected naïve mice was ineffective. Based on pharmacokinetic analysis, the driver of efficacy is the maintenance of a minimal efficacious concentration of approximately 100 ng/ml (based on subcutaneous treatment at 25 mg/kg in mice). From animal models, the human efficacious dose is predicted to range from 1.5 to 4.1 mg/kg. Such a dose has already been proven to be safe in phase 1 clinical trials. Oxfendazole therefore has potential to be efficacious for treatment of human filariasis without causing adverse reactions due to drug-induced microfilariae killing.